2013
DOI: 10.1039/c3ra43165g
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of magnetic and electrical order in the new perovskite-like (C3N2H5)[Mn(HCOO)3] formate

Abstract: In this work we further the structural characterization of the recently discovered (C 3 N 2 H 5 )[Mn(HCOO) 3 ] metal-organic framework with perovskite-like structure, and we present its magnetic and dielectric properties up to 350 K. At low temperature, the C 3 N 2 H 5 + imidazolium cations, that sit oblique within the cavities of the [Mn(HCOO) 3 ] À framework structure, show a cooperative order resulting in an antiparallel arrangement of their electrical dipole moments. Very interestingly, it is only above 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 28 publications
6
58
1
Order By: Relevance
“…Such a small canting is in general strongly sensitive to temperature, magnetic field and the strength of the coupling between the magnetic ions, and small changes in these parameters may lead to complex magnetic behavior. 18 The small saturation magnetization of DMNaFe, comparable to that found in other metal formates templated by dimethylammonium, 8,9 ammonium, 3 or imidazolium, 19 is consistent with the spin-canted mechanism of the long-range magnetic ordering in DMNaFe.…”
Section: Dielectric Propertiessupporting
confidence: 59%
See 1 more Smart Citation
“…Such a small canting is in general strongly sensitive to temperature, magnetic field and the strength of the coupling between the magnetic ions, and small changes in these parameters may lead to complex magnetic behavior. 18 The small saturation magnetization of DMNaFe, comparable to that found in other metal formates templated by dimethylammonium, 8,9 ammonium, 3 or imidazolium, 19 is consistent with the spin-canted mechanism of the long-range magnetic ordering in DMNaFe.…”
Section: Dielectric Propertiessupporting
confidence: 59%
“…22 Here it is interesting to note that order-disorder phase transitions in the family of perovskite-type MOFs of formula [cat][M(HCOO) 3 ], where cat denotes an organic cation, were reported for cat = DMA + , azetidinium, formamidinium, imidazolium, hydrazinium, or ethylammonium. 6,7,9,11,12,19,21,26 For the manganese analogues, the phase transition temperature upon cooling was the lowest for DMA + (181 K) and the highest for imidazolium (435 K), 9,19 and Fig. 7 Raman spectra in the spectral range 25-500 cm −1 .…”
Section: Papermentioning
confidence: 97%
“…Many of [cat][M(HCOO)3] compounds undergo structural phase transitions, which are often associated with the appearance of electric order and pronounced dielectric anomalies [8][9][10][11][12][13][14][15][16][17]. It is worth to mention that up to now the highest phase transition temperature (435 K) in the family of dense MOFs has been found for imidazolium analogue, [C3N2H5][Mn(HCOO)3] [14].…”
Section: Introductionmentioning
confidence: 99%
“…The best known examples are compounds of general formula [cat][M(HCOO)3], where M = Mn, Ni, 3 Co, Fe, and cat denotes ammonium, methylammonium, dimethylammonium (DMA), guanidinium (Gua), formamidinium (FMD) or azetidinium cation [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Many of [cat][M(HCOO)3] compounds undergo structural phase transitions, which are often associated with the appearance of electric order and pronounced dielectric anomalies [8][9][10][11][12][13][14][15][16][17]. It is worth to mention that up to now the highest phase transition temperature (435 K) in the family of dense MOFs has been found for imidazolium analogue, [C3N2H5][Mn(HCOO)3] [14].…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Jain et al reported a multiferroic behavior in a family of perovskite MOFs8. This finding has stimulated considerable experimental and theoretical efforts to search for new multiferroic materials in MOFs910112324252627282930. However, the cross coupling between magnetic and electric orders in MOFs, an extremely important feature required for applications, has not been verified in previous studies, which has casted doubt on the promise of organic multiferroics.…”
mentioning
confidence: 99%